Wind erosion escalation in western Slovakia driven by climate and land use and land cover shifts - Fahime, Nikseresht; Lenka, Lackoóvá; Saleh, Yousefi (Geoderma Regional, 2024)
Wind erosion is a major cause of soil degradation and air pollution and is influenced by climate and land use factors. Understanding the mechanisms behind wind erosion dynamics is crucial for mitigating its harmful effects. This study employs an integrated approach, combining the Analytic Hierarchy Process (AHP) methodology and local knowledge, to comprehensively assess wind erosion in the western region of Slovakia from 2001 to 2021. Using GIS-based AHP, the study assessed the spatial distribution of areas at high risk of wind erosion based on six parameters: wind speed, surface dryness, land use, land cover, soil texture, and field slope. A multicollinearity test was conducted to examine the collinearity of the chosen factors, and it was seen that none of the factors were compromised by multicollinearity. The results showed a significant increase in the risk of wind erosion in the study area over the past 20 years, with very high erosion risk in 2007, 2014, and 2021 increasing by 37 %, 86 %, and 128 %, respectively, compared to 2001. Statistical analyses confirm the significant impact of surface dryness, wind speed, land use, and land cover on wind erosion, emphasizing the need for targeted strategies to mitigate erosion risk. The regression analysis underscores the negative relationship between land use and wind erosion, emphasizing the pivotal role of land management in erosion prevention. These findings contribute valuable insights to the discourse on sustainable land use practices and erosion mitigation, particularly in the context of evolving climate dynamics. [Display omitted]